Bhrunaha dan Krisis Kesadaran Moral dalam Perspektif Hindu - I Wayan Astraguna (Fakultas Dharma Duta dan Brahma Widya, 2026)
Bhrunaha, or abortion, in Hindu teachings is regarded not merely as a moral violation, but as a reflection of a crisis of moral consciousness in modern human life. This study aims to examine the phenomenon of bhrunaha from the perspective of Hindu philosophy through ontological, epistemological, and axiological dimensions. The research employs a qualitative method using a library research approach with descriptive-interpretative analysis. Data sources were obtained from Hindu philosophical texts, scholarly literature, and relevant social and psychological theories, including social construction theory, symbolic interactionism, and desire theory. The findings reveal that ontologically, life in Hindu teachings is understood to exist since conception, making bhrunaha a violation of the sacred essence of life. Epistemologically, the weakening of moral consciousness is influenced by permissive social constructions and shifts in the meaning of sexuality within modern social interactions. Meanwhile, axiologically, the phenomenon reflects a transformation of values from sacred orientations toward pragmatic considerations, where moral decisions are often shaped by social pressure, fear, and the domination of desire. The integration of these theoretical perspectives demonstrates that bhrunaha cannot be understood solely as an individual moral issue, but also as the result of interactions between social reality, symbolic meaning, and psychological impulses in modern society. This study concludes that the phenomenon of bhrunaha reflects a crisis of moral consciousness in which dharma no longer functions as the primary foundation in human moral decision-making.